1972
DOI: 10.1111/j.1365-2362.1972.tb00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Study by Direct Calorimetry of Thermal Balance on the First Day of Life

Abstract: Abstract. Using a gradient layer direct calorimeter, total heat losses were measured in 69 full term new‐borns at 5 different ambient temperatures (TA): 28, 30, 32, 34 and 36° C. The relative humidity of the air was kept constant at 50%. Oesophageal temperature (Teg) and mean skin temperature (T̄s) were continuously recorded. All experiments lasted at least one hour. The mean total heat loss was at 28° C: 3.55 W/kg; at 30° C: 2.97 W/kg; at 32° C: 2.35 W/kg; at 34° C: 1.92 W/kg and at 36° C: 2.05 W/kg. Dry hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…The fetus is a metabolically active organism whose temperature closely follows maternal temperature, forming a heat clamp, and remains 0.5 1C higher. [27][28][29] This heat clamp creates a steady state and provides the fetus with a thermostable environment. 30 Although the fetus develops in a warm and thermostable environment, its basal heat production (kcal kg À1 ) is about twice that of adult levels.…”
Section: Pathophysiology Of Neonatal Hypothermiamentioning
confidence: 99%
“…The fetus is a metabolically active organism whose temperature closely follows maternal temperature, forming a heat clamp, and remains 0.5 1C higher. [27][28][29] This heat clamp creates a steady state and provides the fetus with a thermostable environment. 30 Although the fetus develops in a warm and thermostable environment, its basal heat production (kcal kg À1 ) is about twice that of adult levels.…”
Section: Pathophysiology Of Neonatal Hypothermiamentioning
confidence: 99%
“…Sweating has been reported to occur in newborn babies with a core temperature of 37.3˚C or more in combination with a temperature difference between core and mean skin temperature of less than 1˚C. 4 …”
Section: Heat Lossesmentioning
confidence: 99%
“…[2][3][4][5] This study is descriptive, aiming to define temperature variations of the neonate during normal care in the first two days of life in a maternity ward of a western European country. The following were recorded.…”
mentioning
confidence: 99%
“…Furthermore, Ryser and J^quier [30] found that the metabolic rate continuously diminished as the environment became by 2° or 4° warmer than the neutral temperature.…”
Section: Metabolic Ratementioning
confidence: 99%